2022
DOI: 10.1155/2022/7162623
|View full text |Cite
|
Sign up to set email alerts
|

Long Noncoding RNA LINC01554 Inhibits the Progression of NSCLC Progression by Functioning as a ceRNA for miR-1267 and Regulating ING3/Akt/mTOR Pathway

Abstract: Objectives. This study focused on the biological functions and mechanisms of action of LINC01554 in nonsmall cell lung cancer (NSCLC). Methods. The expression and prognostic values of LINC01554 in NSCLC were evaluated using The Cancer Genome Atlas datasets. MTT, colony formation, wound healing, transwell, and in vivo assays were performed to investigate the role of LINC01554 in NSCLC. The related protein expression levels were measured via western blotting. Bioinformatic analysis was conducted to predict targe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 29 publications
0
4
0
Order By: Relevance
“…After searching the literatures, the roles of lncRNA HAND2-AS1 in liver cancer have been fully reported previously ([ 11 , 18 ]), while no studies have reported the specific roles of lncRNA RP11-557H15.4 in human diseases. Additionally, for lncRNA LINC01554, some studies have reported its roles in other cancers, such as NSCLC [ 19 ], laryngeal squamous cell carcinoma [ 20 ], and esophageal squamous cell carcinoma [ 21 ], but its action mechanisms in HCC are still unclear. Additionally, it was also found that compared with the paracancerous tissues, the level of LINC01554 was significantly decreased in the cancer tissues ( P < 0.05, Fig.…”
Section: Resultsmentioning
confidence: 99%
“…After searching the literatures, the roles of lncRNA HAND2-AS1 in liver cancer have been fully reported previously ([ 11 , 18 ]), while no studies have reported the specific roles of lncRNA RP11-557H15.4 in human diseases. Additionally, for lncRNA LINC01554, some studies have reported its roles in other cancers, such as NSCLC [ 19 ], laryngeal squamous cell carcinoma [ 20 ], and esophageal squamous cell carcinoma [ 21 ], but its action mechanisms in HCC are still unclear. Additionally, it was also found that compared with the paracancerous tissues, the level of LINC01554 was significantly decreased in the cancer tissues ( P < 0.05, Fig.…”
Section: Resultsmentioning
confidence: 99%
“…In lung carcinomas, differential expression of lncRNAs has been observed depending on the cancer type. Representative cases are SLC9A3-AS1, reported upregulated; LINC01554 and GABPB1 reported downregulated in NSCLC tissues [166][167][168], while RBPMS-AS1 expression was found to be diminished in lung adenocarcinoma [169]. Other studies have shown the reduced expression of LINC00294 in colorectal carcinoma tissues [170], while SLFNL1-AS1, KCNQ1OT1, NEAT1, XIST, AC016876.2, AC026362.1 were found to be downregulated in colon cancer cell lines [171].…”
Section: Discussionmentioning
confidence: 96%

miRNAs as Interconnectors between Obesity and Cancer

González-Sánchez,
Granados-López,
López-Hernández
et al. 2024
ncRNA
“…In several types of cancer, most lncRNAs are either up- or downregulated. These lncRNAs favor all stages of tumor development through the promotion of mRNA expression and constancy [ 253 ], by favoring mRNA stability [ 254 ], or by modulating miR [ 254 , 255 , 256 , 257 , 258 , 259 , 260 , 261 , 262 , 263 , 264 , 265 , 266 , 267 , 268 , 269 , 270 , 271 , 272 , 273 , 274 , 275 , 276 , 277 , 278 , 279 , 280 , 281 , 282 , 283 , 284 , 285 , 286 , 287 , 288 , 289 , 290 , 291 , 292 , 293 , 294 , 295 , 296 , 297 , 298 , 299 , 300 ]. The aberrant phenotype is the result of the modulation of typical pathways playing key roles in cell survival [ 255 , 259 , 263 , 265 , 283 ], apoptosis [ <...…”
Section: Analyzing Cernets For Diagnosis and Targeting Them For Thera...mentioning
confidence: 99%
“…Another important pathway in cancer is the phosphoinositide 3-kinase-AKT-mammalian target of the rapamycin (PI3K-AKT-mTOR) pathway, which is frequently hyperactivated in cancer and is essential for tumor cell growth and survival [ 61 ]. Indeed, several lncRNAs such as HOTAIR, HOXD-AS1, LINC00511, H19, and LINC01554, by targeting specific miRs, increase the expression of AKT and mTOR, promoting aberrant phenotypes [ 262 , 264 , 271 , 274 , 278 , 287 , 296 ].…”
Section: Analyzing Cernets For Diagnosis and Targeting Them For Thera...mentioning
confidence: 99%